Türk Medeni Hukukunda kanuni önalım (Şuf’ a) hakkı (MK. md. 659) - Ciğerim, Ersin (My University, 2001)
Medeni Kanunun 659.maddesinde düzenlenen “kanuni önalım hakkı” müşterek mülkiyete tabi bir taşınmazın paydaşlarından birinin payını bir üçüncü şahsa satması halinde, diğer paydaşlara aynı şartlarla bu payın alıcısı olabilme yetkisi veren, eşyaya (paya) bağlı bir yenilik doğuran haktır. Kanuni önalım hakkı, taşınmaz mülkiyetinin “kanundan doğan”, “özel hukuk nitelikli” ve “dolaylı” bir sınırlamasıdır. Müşterek mülkiyet ilişkisinin kurulmasıyla kanun icabı (kendiliğinden) doğan önalım hakkının kullanılabilmesi için önalım olayının gerçekleşmesi yani paydaşlardan birinin payını, (paydaşlar dışında) bir üçüncü kişiye satması şarttır. Bu satım sözleşmesinin “tam” ve “geçerli” bir sözleşme olması gerekir. Satış bedelinin gerçek bedele göre düşük gösterildiği “bedelde muvazaa” halinde, önalım hakkı, MK.md.2 gereği “rayiç bedel” üzerinden kullanılabilmelidir. Önalım hakkının kullanılması birer olumsuz koşul olarak, bir aylık hak düşürücü süre ve on yıllık azami sürenin geçirilmemiş olmasına, hakkın kendisinden veya onun kullanılmasından feragat edilmemiş olmasına ve hakkın kötüye kullanılması yasağının ihlal edilmemiş olmasına bağlıdır. Önalım hakkı, tek taraflı ve karşı tarafa varması gerekli bir yenilik doğuran işlem ile kullanılır. Hakkın kullanıldığı yenilik doğurucu beyanın muhatabı (önalım yükümlüsü), kanundan doğan eşyaya bağlı borç ilişkisinin sonucu olarak, önalım olayından sonra payın mülkiyeti devredilmişse alıcı üçüncü kişi, devredilmemişse satıcı paydaştır. Hakkın kullanılmasıyla, önalım hakkı sahibiyle önalım yükümlüsü arasında, ilk satım sözleşmesinin koşulları altında yeni bir satım ilişkisi doğar. Önalım hakkı satıştan uzun bir süre sonra kullanılmışsa, önalım bedeli tapudaki bedele göre değil, hakkın kullanıldığı tarihteki gerçek değere göre belirlenmelidir. Yeni ilişkideki satıcı (önalım yükümlüsü), payın mülkiyetini devir borcunu rızaen ifa etmezse, önalım hakkı sahibi MK.md.642 uyarınca açacağı bir ifa davası sonucu verilecek yenilik doğuran karar ile payın mülkiyetini iktisap edecektir.

THE RIGHT OF THE LEGAL PREEMPTION IN THE TURKISH CIVIL CODE (T.C.C.659) By giving the other co-owners of collective held properties the right to acquire the shares of another co-owner at the same conditions in case this partial-owner a selling his/ her share to third parties, the preemption right which is set in Civil Code 659 is a property attached right giving birth to a new development. The legal preemption right is an indirect limitation of property rights and is arising from law and has private law attributes. In order to use the preemption right which arises legally by establishing a collective property ownership, one of the collective owners must have sold his/ her share to third parties other than any of the collective owners. This sales contract must be a copmlete and valid contract. In a collusion over the sales price where the sales price is shown lower than the fair market value, the preemption right should be usable – due to Civil Code Articte 2- at the fair market price. The use of preemption right depends on the conditions that the one month right nullifying time and maximum of ten years time has not elapsed, that one has not given up the right or the use of the right and that the interdict of misusing the right has not been broken. The preemption right is used through a transaction which is unilateral and which arises a new development that must reach the other party of the right. The addressee of the declaration is the third person who is buying the share if ownership of the share has been transfered after the preemption and the addressee is the selling collective owner if the ownership has not been transfered. With the use of the right there arises a sales relationship between the preemption right holder and the addressee under the conditions of the first sales conract. If the preemption right has been used after a long time since the sale, the preemption value has to be set not according to value written on the property-register, but according to fair market value on the date the preemption right is used. If the addressee does not fulfil his liability of transfering the ownership of the share willingly, the preemption right holder will acquire the ownership of the share by a court decision according to T.C.C. 642.
Keywords: Hukuk; MEDENİ HUKUK_TÜRKİYE; Özel hukuk